Early assessment of effects of dam removal on abiotic fluxes of the Selune River, France - Fovet, Ophelie; Meric, François; Crave, Alain; Cador, Jean-Michel; Rollet, Anne-Julia (Frontiers in Environmental Science, 2023)
The Water Framework Directive set for European Union countries the objective of restoring the ecological and/or sediment continuity of rivers, as the latter is relevant for providing suitable habitats for the former. Indeed, abiotic fluxes and variables shape riverine ecological habitats and are likely to be modified by barriers such as dams. Two dams were removed from the Selune River (northwestern France) from spring 2017 to summer 2022. The objective of this study was to describe and quantify how the dams modified abiotic parameters and fluxes, as well as the dynamics of these fluxes during dam removal. We monitored coarse and fine sediments, water temperature and nutrient concentrations in the Selune River from upstream to downstream of the dams from 2015-2023. The results showed that coarse sediments of the riverbed are a legacy and that current hydrodynamic conditions are not sufficient to move them much, with or without the dams. In addition, it appears that at this early stage after the removal some downstream parameters, especially nutrient concentrations and water temperature, have already converged towards upstream signals, while fine sediment stored in the dam's reservoirs are still destocking. Restoring ecological continuity of the Selune River will involve dynamics of abiotic parameters over longer time scales, in response to removal of the dams, and over larger spatial scales, in response to climate and other global changes.